ENVIRONMENTAL ORIENTATION OF ENERGY POLICY OF THE EU AND UKRAINE - КУЗНЄЦОВА, О. О.; ЯСТРЕМСЬКА, Л. С.; КОРНІЄНКО , І. М.; БАРАНОВСЬКИЙ , М. М. (Technologies and Engineering, 2023)
Purpose. The purpose of the work is to study the development of integration of environmental goals in the energy policy of the EU and Ukraine, to identify some problematic issues that characterize the current state of the energy greening process, and to find appropriate solutions for solving these problems. Methodology. Analysis of regulatory legal acts of the EU and Ukraine in the field of renewable energy and energy efficiency, and literary sources, which highlight the problems of the process of “green” energy development. Findings. An analysis of the introduction of environmental goals to the energy policy and legislative acts of the EU and Ukraine was performed. The state of adaptation of national legislation in the field of energy to the requirements of a number of EU Directives has been studied. The main tasks to be performed by Ukraine in connection with the announcement of the European Green Deal and ambitious plans for reforming the EU energy sector with the aim of achieving climate neutrality in 2050 are revealed. Ways of effective involvement of Ukraine in policy formation within the framework of the European Green Deal are considered. Originality. The systematization and comparison of the regulatory and legal framework of the EU and Ukraine from the point of view of the integration of environmental goals into the energy policy was carried out, and problematic aspects of state regulatory and legal regulation in the field of renewable energy and energy efficiency in the context of the European integration vector of Ukraine’s development are outlined. Practical value. Proposals regarding active cooperation with the EU at all stages of the development of regulatory and legal acts and taking into account new environmentally oriented initiatives of the EU in the field of energy during the development of national action programs for the development of renewable energy will allow timely adaptation of national legislation to modern challenges and more effective implementation of the principles of sustainable development.